Psychological interventions for people with psychotic experiences: A systematic review and meta-analysis of controlled and uncontrolled effectiveness and economic studies. (July 2020) - Soneson, Emma; Russo, Debra; Stochl, Jan; Heslin, Margaret; Galante, Julieta; Knight, Clare; Grey, Nick; Hodgekins, Joanne; French, Paul; Fowler, David; Lafortune, Louise; Byford, Sarah; et al.
Objective: Many people with psychotic experiences do not develop psychotic disorders, yet those who seek help demonstrate high clinical complexity and poor outcomes. In this systematic review and meta-analysis, we evaluated the effectiveness and cost-effectiveness of psychological interventions for people with psychotic experiences. Method: We searched 13 databases for studies of psychological interventions for adults with psychotic experiences, but not psychotic disorders. Our outcomes were the proportion of participants remitting from psychotic experiences (primary); changes in positive and negative psychotic symptoms, depression, anxiety, functioning, distress, and quality of life; and economic outcomes (secondary). We analysed results using multilevel random-effects meta-analysis and narrative synthesis. Results: A total of 27 reports met inclusion criteria. In general, there was no strong evidence for the superiority of any one intervention. Five studies reported on our primary outcome, though only two reports provided randomised controlled trial evidence that psychological intervention (specifically, cognitive behavioural therapy) promoted remission from psychotic experiences. For secondary outcomes, we could only meta-analyse trials of cognitive behavioural therapy. We found that cognitive behavioural therapy was more effective than treatment as usual for reducing distress (pooled standardised mean difference: −0.24; 95% confidence interval = [−0.37, −0.10]), but no more effective than the control treatment for improving any other outcome. Individual reports indicated that cognitive behavioural therapy, mindfulness-based cognitive therapy, sleep cognitive behavioural therapy, systemic therapy, cognitive remediation therapy, and supportive treatments improved at least one clinical or functional outcome. Four reports included economic evaluations, which suggested cognitive behavioural therapy may be cost-effective compared with treatment as usual. Conclusion: Our meta-analytic findings were primarily null, with the exception that cognitive behavioural therapy may reduce the distress associated with psychotic experiences. Our analyses were limited by scarcity of studies, small samples and variable study quality. Several intervention frameworks showed preliminary evidence of positive outcomes; however, the paucity of consistent evidence for clinical and functional improvement highlights a need for further research into psychological treatments for psychotic experiences. PROSPERO protocol registration number: CRD42016033869